2018
DOI: 10.1111/andr.12492
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria, glycogen, and lipid droplets in skeletal muscle during testosterone treatment and strength training: a randomized, double‐blinded, placebo‐controlled trial

Abstract: Low testosterone levels in aging men are associated with insulin resistance. Mitochondrial dysfunction, changes in glycogen metabolism, and lipid accumulation are linked to insulin resistance in skeletal muscle. In this randomized, double-blinded, placebo-controlled study, we investigated the effects of six-month testosterone replacement therapy (TRT) and strength training (ST) on mitochondrial, glycogen, and lipid droplet (LD) content in skeletal muscle of aging men with subnormal bioavailable testosterone (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
3
4
0
Order By: Relevance
“…Our data also corroborated the pivotal role of T in maintaining the homeostasis of mitochondria, the most energetically active organelles in the eukaryotic cells [85]. Previous studies, both in animal models and in humans, demonstrated that androgens stimulate glucose utilization and ATP production, as well as mitochondrial cytochrome c oxidase activity in muscle [86][87][88], and in several other tissues and cell types [89][90][91][92]. However, to our knowledge, this is the first demonstration that in vivo TTh is associated with a healthier phenotype of human preadipocytes.…”
Section: Discussionsupporting
confidence: 87%
“…Our data also corroborated the pivotal role of T in maintaining the homeostasis of mitochondria, the most energetically active organelles in the eukaryotic cells [85]. Previous studies, both in animal models and in humans, demonstrated that androgens stimulate glucose utilization and ATP production, as well as mitochondrial cytochrome c oxidase activity in muscle [86][87][88], and in several other tissues and cell types [89][90][91][92]. However, to our knowledge, this is the first demonstration that in vivo TTh is associated with a healthier phenotype of human preadipocytes.…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with evidence demonstrating increased whole body lipid oxidation in hypogonadic men treated with testosterone (42). Whereas increases in the proportion of the mitochondrial fraction of the muscle cell related to increases in serum testosterone, there was no apparent change in the number or activity of mitochondrial enzymes, genes involved in biogenesis, or lipid metabolism (24,42). Thus the exact role of excess or supplemental testosterone in mitochondrial function per se remains unclear.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, despite these significant variations in serum hormonal levels, the biochemical mechanism by which Te affects body composition is not completely understood. The androgens' capability to increase LBM, and consequently muscle mass, has been previously envisaged in different experimental settings [62,63]. In fact, Te is able to stimulate lipolysis in animal models [64], as well as in human subcutaneous adipose tissue, in which both a Te-induced inhibition of lipoprotein lipase and an activation of the hormone sensitive lipase were observed [65].…”
Section: Discussionmentioning
confidence: 99%